Added Value Analysis of Processed Cassava Products (Gethuk and Balung Kethek) - Astuti, Eni; Uchyani Fajarningsih, Rhina; Setyowati, Nuning (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 3 (2021): Vol.15, No.3, 2021DO - 10.24843/SOCA.2021.v15.i03.p11, 2021)
Agroindustry plays an important role in increasing the added value of agricultural products which are perishable and have short shelf life. The added value is obtained from the processing process which raises costs and forms new prices along with greater profits. This study aims to analyze the profits, business efficiency, and added value of Gethuk and Balung Kethek in the Gethuk Semar Industry. The basic method of this research is descriptive method. The respondents were determined using non-probability sampling methods, purposive sampling technique, and key informants. Added value analysis was done by Hayami method and the business efficiency was analyzed using the R / C ratio and the B / C ratio. The results of the analysis show that the processing of cassava into Gethuk and Balung Kethek is profitable, efficient, and has added value. Gethuk provides benefits, business efficiency, and higher added value than Balung Kethek. Based on the results of this study, it is advised to optimize the use of cost inputs. The cost of cooking oil in Balung Kethek is too immense. The Gethuk Semar Industry may use high-atioxidant cooking oil that can be used several times in the production process.